Short films from a small nation Danish informational cinema 1935-1965 - Thomson, C. Claire (Traditions in world cinema., 2018)
"For three decades, state-sponsored short filmmaking educated Danish citizens, promoted Denmark to the world, and shaped the careers of renowned directors like Carl Th. Dreyer. The first book-length study in English of a national corpus of state-sponsored informational film, this book traces how Danish shorts on topics including social welfare, industry, art and architecture were commissioned, funded, produced and reviewed from the inter-war period to the 1960s. Examining the life cycle of a representative selection of films, and discussing their preservation and mediation in the digital age, this book presents a detailed case study of how informational cinema is shaped by, and indeed shapes, its cultural, political and technological contexts."--Back cover.